ON THE DIRECT AND INVERSE PROBLEMS FOR PERIODIC STURM-LIOUVILLE OPERATOR - ABDULKAREEM, HEZHA HUSSNI (Fırat Üniveristesi, 2020)
Bu çalışmada, periodik Sturm-Liouville operatoru ve periodik Dirac sistemi için spektral analizin bazı problemleri incelenmişdir. İlk olarak Sturm-Liouville operatoru için periyodik ve semi periodik problemler ve Liapunove fonksoyonu (Hille diskriminantı) tanımlanır. Daha sonra N-bölgeli periodik potansiyeller için ters meselenin çözümü farkli yöntemle verilir. İkincisi, periodik potansiyel içeren kanonik Dirac sistemi ele alınır ve bu durumda spektral analizin düz ve ters problemleri ile ilgili daha detaylı bilgi verilir. Özellikle N-bölgeli periodik potansiyeller durumunda dönüşüm operatörü ve Hill diskriminantından faydalanarak ters meselenin çözümüne ait yeni teorem ispat edilir. Anahtar Kelimeler: Sturm-Liouville Operatörü, Periyodik ve Yarı Periyodik sınır koşulları, Çeviri Operatörü, Genel Dejenerasyon, Dirac operatörü.

In this research, some problems of spectral analysis for periodic Sturm-Liouville operator and periodic Dirac system are investigated and explained. Firstly, periodic, semi-periodic problems and Lyapunov function (Hill's discriminant) are defined for the Sturm-Liouville operator. Then, the solution of the inverse problem for N- zoned periodic potentials is given by different methods. Second, the canonical Dirac system with periodic potential is discussed and in this case more detailed information is given about the direct and inverse problems of spectral analysis. Especially in the case of N-zone periodic potentials, new theorem of the solution of the inverse problem is proved by making use of the transformation operator and Hill discriminant. Keywords: Sturm-Liouville Operator, Periodic and Semi-Periodic boundary conditions, Transformation Operator, General Degeneracy, Dirac operator.
Periyodik Sturm-Liouville operatörü için düz ve ters problemler
Keywords: Matematik